2000
DOI: 10.1038/sj.leu.2401963
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of the Italian Association of Pediatric Hematology and Oncology (AIEOP) Acute Lymphoblastic Leukemia Studies, 1982–1995

Abstract: The first multicentric approach to childhood acute lymphoblastic leukemia (ALL) treatment in Italy started in the early 1970s when the Associazione Italiana di Ematologia ed Oncologia Pediatrica (AIEOP) was founded. Since then the AIEOP has conducted nationwide chemotherapy protocols. Results obtained in three different periods (1982-1986, 1987-1990, 1991-1995) are reported here. Treatment schedules have been characterized by a progressive intensification of systemic therapy and by a progressive substitution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
10

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 12 publications
1
61
1
10
Order By: Relevance
“…Yet, 70% of them received an intensive, BFM-based chemotherapy. 21 Leukemia relapse occurred mainly in the bone marrow; the likely explanation for this is the reduced treatment intensity induced by inherent risk of infection in these constitutively immune-compromised patients. This is in keeping with the finding of the BFM group reporting that among 61 DS patients from trials ALL-BFM 81, 83, 86, and 90, EFS was comparable to that of the non-DS group once they received treatment with no major modifications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, 70% of them received an intensive, BFM-based chemotherapy. 21 Leukemia relapse occurred mainly in the bone marrow; the likely explanation for this is the reduced treatment intensity induced by inherent risk of infection in these constitutively immune-compromised patients. This is in keeping with the finding of the BFM group reporting that among 61 DS patients from trials ALL-BFM 81, 83, 86, and 90, EFS was comparable to that of the non-DS group once they received treatment with no major modifications.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Whereas the traditional cutoff age for eligibility had been younger than 15 years, starting with the most recent studies, AIEOP-ALL-95 and AIEOP-BFM-ALL-2000, the cutoff age was extended to younger than 18 years.…”
Section: Patientsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] In the earlier studies conducted in the 70s, all patients received a relatively low-intensity chemotherapy and cranial radiotherapy (CRT). In Study 82, patients were stratified into three risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…It provides 15-year updated figures for studies 82,87,88,91 reported earlier in Leukemia 13 and newly presents long-term results of Study 95.…”
Section: Introductionmentioning
confidence: 99%
“…The intent was to identify effective treatment for certain well-defined subsets of patients. This unprecedented effort resulted in 12 informative articles published together in the December 2000 issue of Leukemia, [5][6][7][8][9][10][11][12][13][14][15][16] providing valuable clues to advance the cure rate in future trials.…”
Section: Introductionmentioning
confidence: 99%